Pengaruh Gaya Hidup dan Kesadaran Halal Terhadap Minat Beli Produk Fashion Pada Era New Normal di Surabaya - Muhammad Rizky Irza Fachruddin; Moch. Khoirul Anwar (CV ODIS, 2022)
This pandemic situation makes everyone in the world have to readjust their lifestyle to survive and makes everyone have to stay at home. So the appearance and the clothes used are no longer a priority because they rarely leave the house. The purpose of this study was to determine the effect of lifestyle and halal awareness on interest in buying fashion products in the new normal era in Surabaya. The approach used in this study is a quantitative descriptive approach with multiple linear regression data analysis techniques. The result of this research is that lifestyle and halal awareness have no partial positive effect but simultaneously positive effect on the interest in buying fashion products of Surabaya society in the new normal era. Many variables influence people's buying interest in fashion products in this new normal era. This research has a contribution, one of which is for business actors in the fashion sector to add insight and create strategies for situations like this.